2022
DOI: 10.3389/fmicb.2022.799333
|View full text |Cite
|
Sign up to set email alerts
|

Population Differences and Host Species Predict Variation in the Diversity of Host-Associated Microbes in Hydra

Abstract: Most animals co-exist with diverse host-associated microbial organisms that often form complex communities varying between individuals, habitats, species and higher taxonomic levels. Factors driving variation in the diversity of host-associated microbes are complex and still poorly understood. Here, we describe the bacterial composition of field-collected Hydra, a freshwater cnidarian that forms stable associations with microbial species in the laboratory and displays complex interactions with components of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…Since the French and Hungarian laboratories have exchanged hydra strains in the past, we cannot exclude the hypothesis of a previous contamination with these Chlamydia strains before this study. Interestingly, there is no evidence of this bacterium in the natural microbiome of hydras sampled directly in the wild 28 , which can indicate either that these bacteria are rare or variably detectable. In addition, it is also possible that these bacteria became more abundant after few generations in the lab 21 .…”
Section: Discussionmentioning
confidence: 98%
“…Since the French and Hungarian laboratories have exchanged hydra strains in the past, we cannot exclude the hypothesis of a previous contamination with these Chlamydia strains before this study. Interestingly, there is no evidence of this bacterium in the natural microbiome of hydras sampled directly in the wild 28 , which can indicate either that these bacteria are rare or variably detectable. In addition, it is also possible that these bacteria became more abundant after few generations in the lab 21 .…”
Section: Discussionmentioning
confidence: 98%
“…The H. vulgaris bacterial community consists of the genera Rhodoferax and Legionella with less than 20% of other genera. Curvibacter which are often present at relative abundances >70% in H. vulgaris ( Franzenburg et al, 2013 ; Taubenheim et al, 2022 ) were not observed here. This may potentially be linked to the primer sets used in the studies.…”
Section: Resultsmentioning
confidence: 53%
“…and microbiota composition has strong effects on Hydra physiology (reviewed in: Taubenheim et al, 2022). This is all the more likely because we here detected a substantial drop in the survival rate of strain C2/7 relative to our previous study (Ngo et al, 2021).…”
Section: Survivalmentioning
confidence: 50%
“…Genetic differences among our strains are likely to be low (Miklós et al, 2021), and the laboratory conditions under which they were maintained were identical. However, they might differ in the composition of their associated microbiota (something that we currently do not know), and microbiota composition has strong effects on Hydra physiology (reviewed in: Taubenheim et al, 2022). This is all the more likely because we here detected a substantial drop in the survival rate of strain C2/7 relative to our previous study (Ngo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%